2021
DOI: 10.1177/03611981211014529
|View full text |Cite
|
Sign up to set email alerts
|

Household Evacuation Planning and Preparation for Future Hurricanes: Role of Utility Service Disruptions

Abstract: We analyzed data from a survey administered to 1,212 respondents living in superstorm Hurricane Sandy-affected areas. We estimated the effect of having experienced hurricane-induced disruptions to utility services, such as electricity, water, gas, phone service, and public transportation, on having an evacuation plan. Around 39% of respondents reported having an evacuation plan in case a hurricane affects their neighborhood this year. Respondents who had experienced disruptions to electricity supply had an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Researchers distribute questionnaires to the targeted populations to gather information about the impact of disasters on households and communities, and the mitigation behaviors they undertake to respond to disasters. For example, Coleman et al (2020) studied the anatomy of susceptibility to different infrastructure service disruptions based on household survey data from three major hurricanes (Harvey, Florence, and Michael) between 2017and 2018and Halim et al (2021 found that utility services disruption experienced by households during Hurricane Sandy is a significant factor that influences future hurricane preparation and planning. Utilizing post-Harvey household survey, Dong et al (2020) evaluated physical vulnerability due to critical facilities disruptions and the associated community tolerance level in urban flooding.…”
Section: Survey Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers distribute questionnaires to the targeted populations to gather information about the impact of disasters on households and communities, and the mitigation behaviors they undertake to respond to disasters. For example, Coleman et al (2020) studied the anatomy of susceptibility to different infrastructure service disruptions based on household survey data from three major hurricanes (Harvey, Florence, and Michael) between 2017and 2018and Halim et al (2021 found that utility services disruption experienced by households during Hurricane Sandy is a significant factor that influences future hurricane preparation and planning. Utilizing post-Harvey household survey, Dong et al (2020) evaluated physical vulnerability due to critical facilities disruptions and the associated community tolerance level in urban flooding.…”
Section: Survey Methodsmentioning
confidence: 99%
“…(2020) studied the anatomy of susceptibility to different infrastructure service disruptions based on household survey data from three major hurricanes (Harvey, Florence, and Michael) between 2017 and 2018 and Halim et al. (2021) found that utility services disruption experienced by households during Hurricane Sandy is a significant factor that influences future hurricane preparation and planning. Utilizing post‐Harvey household survey, Dong et al.…”
Section: Review Of Supporting Methodsmentioning
confidence: 99%
“…The impact of utility disruption on wellbeing also depends on evacuation plans Halim et al (2021). calculated the hurricane-induced disruption in areas affected by Hurricane Sandy and concluded that individuals with power outages and financial losses were more likely to evacuate during the hurricane.…”
mentioning
confidence: 99%
“…Mass hurricane evacuations lead to high traffic congestion and possible damage to road networks ( 68 ). It is essential for social scientists and community planners to better understand people’s hurricane evacuation behavior to devise an effective evacuation plan for coastal residents ( 9, 10 ).…”
mentioning
confidence: 99%